Rediscovering James Mark Baldwin - Calandrini, Anna Rita; Marsico, Giuseppina (Psychology Hub, 2020)
James Mark Baldwin played a significant role in the birth of the American experimental psychology at the end of the 19th century. Known for his evolutionary theory that takes his name (The “Baldwin effect”), as well as for the significant influence he exerted on the more famous Piaget in the epistemological field, Baldwin represents a controversial, long-forgotten and only recently rediscovered intellectual figure. After taking his first steps in the field of Scottish mental philosophy, the encounter with German experimentalism led him to apply the scientific method to the study of the development of the child’s mind. Baldwin is among the first scientists to identify the profound link between the evolution of mental faculties and phylogenesis. During the last season of his intellectual life, he devoted himself to the creation of evolutionary epistemology. The present article, after retracing the main stages of his theory illustrates organic selection as a mechanism underlying the ontogenetic and phylogenetic development of the human mind, the laws of habit and accommodation, the role of imitation and the social transmission of “intelligent” functions. This study ends with a reflection on Baldwin’s influence on evolutionary studies during the 20th century, and his oblivion and “rediscoveries”.